Prognostic Value of Electrophysiological Parameters for the Recovery of Motor Functions in Stroke Patients - Kim, S.M.; Kim, J.H.; Kim, B.R.; Hyun, Ch.W.; E. Yo. Han (Нейрофизиология, 2015)
We estimated correlations between baseline electrophysiological parameters and motor functions in patients with subacute stroke, in order to identify their predictive value for motor and functional recovery after a 4-week-long rehabilitation period. Sixty patients with subacute stroke were enrolled. Somatosensory evoked potentials (SSEPs), compound motor action potentials (CMAPs), and sensory nerve action potentials (SNAPs) were recorded, and the amplitude ratios were calculated in the components of these potentials. Clinical parameters consisted of the Korean-modified Barthel index (K-MBI), motricity index (MI), and manual function test (MFT). After the rehabilitation period, these indices were re-evaluated. The ulnar CMAP amplitude was found to significantly correlate with all clinical outcome indices. Additionally, a multivariate linear regression analysis revealed that the ulnar CAMP amplitude ratio was an independent predictor for the baseline MI of the upper extremity and K-MBI. The median SSEP amplitude ratio was an independent prognostic factor for the follow-up MI of the upper extremity, MFT, and follow-up K-MBI. Our results indicate that not only is the median SSEP amplitude ratio a prognostic factor for the motor functions and functional recovery, but also the ulnar CMAP amplitude might be an independent predictor in subacute stroke patients.